1999
DOI: 10.1037/0022-0167.46.3.370
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of grief therapy: A meta-analysis.

Abstract: Subscription orders must be prepaid. (Subscriptions are on a calendar basis only.) Allow 4-6 weeks for delivery of the first issue. Call for international subscription rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
116
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 62 publications
(55 reference statements)
1
116
3
2
Order By: Relevance
“…In a recent meta-analysis, it was found that the greatest benefits of grief therapy are achieved by those who meet a diagnostic criteria for a grief disorder (Wittouck et al, 2011). However, a previous meta-analysis compared studies where participants identified that they needed help with grief to those who were at risk of developing pathology and found that when a person sought help the effects of therapy were larger (Allumbaugh & Hoyt, 1999). Given the possibility that having a diagnosis may affect how the therapy is experienced, then it would be interesting to see if the current findings could be replicated in a study where only those with a grief disorder were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis, it was found that the greatest benefits of grief therapy are achieved by those who meet a diagnostic criteria for a grief disorder (Wittouck et al, 2011). However, a previous meta-analysis compared studies where participants identified that they needed help with grief to those who were at risk of developing pathology and found that when a person sought help the effects of therapy were larger (Allumbaugh & Hoyt, 1999). Given the possibility that having a diagnosis may affect how the therapy is experienced, then it would be interesting to see if the current findings could be replicated in a study where only those with a grief disorder were included.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in other reviews (Allumbaugh & Hoyt, 1999; Schut, Stroebe, van den Bout, & Terheggen, 2001), consistently larger effect sizes and positive outcomes have been reported where participants were self-referred or referred by a general practitioner, when compared to preventative or outreach approaches. These studies suggest that a self-perception of struggling with grief and active treatment seeking results in a benefit from therapy.…”
mentioning
confidence: 88%
“…In the previous meta-analysis, two of these tools were found the most widely used ones in researches and clinical practices: the Inventory of Complicated Grief (ICG) and the Texas Revised Inventory of Grief (TRIG) (Allumbaugh et al 1999). ICG is a validated 19-item instrument which specifically designed to distinguish normal grief reactions from CG, depression and anxiety.…”
Section: Measures In Complicated Griefmentioning
confidence: 99%
“…Several authors have made the statement that some grief intervention efficacy studies turned out to be disappointing and negative (Jordan & Niemeyer 2003:765;Schut et al 2001:705). Jordan and Niemeyer (2003:767-770) refer to studies done by Allumbach and Hoyt (1999), Kato and Mann (1999), as well as Niemeyer (2003). Allumbach and Hoyt (1999) ascribe the low effect of bereavement intervention to the following: a general ineffectiveness of grief counselling, the low statistical power of many of the bereavement studies, or one or more variables that mask the real effects of the intervention.…”
Section: Objectivesmentioning
confidence: 99%
“…Jordan and Niemeyer (2003:767-770) refer to studies done by Allumbach and Hoyt (1999), Kato and Mann (1999), as well as Niemeyer (2003). Allumbach and Hoyt (1999) ascribe the low effect of bereavement intervention to the following: a general ineffectiveness of grief counselling, the low statistical power of many of the bereavement studies, or one or more variables that mask the real effects of the intervention. Kato and Mann (1999) give the following reasons for the disappointing effect: interventions for the bereaved are simply not helpful, they are not powerful enough (too few sessions) and the positive effects are masked by methodological issues (Jordan & Niemeyer 2003:768).…”
Section: Objectivesmentioning
confidence: 99%